New concepts in wage determination - Taylor, George W.; Pierson, Frank Cook (New York : McGraw-Hill, 1957)
Students of labor economics will find this symposium on wage theory and structure a valuable addition to the literature on the subject. Twelve recognized experts in the field, including four past presidents of the Industrial and Labor Research Association, have collaborated to present this lucid and frequently brilliant summary of current wage theory and wage structures. The twelve authors met over a period of three years while the volume was being written. The result is a well-integrated and excellent volume on the various aspects of wage determinations-collective bargaining, interplant and intraplant wage structures, wage differentials and wage movements.
Includes bibliographical footnotes.
rpm 04/04/2018
Loans
Keywords: Wages